Spend-and-tax adjustments and the sustainability of the government's intertemporal budget constraint - Gabriella Deborah Legrenzi; Costas Milas (Center for Economic Studies and ifo Institute (CESifo), 2010)
We apply non-linear error-correction models to the empirical testing of the sustainability of the government's intertemporal budget constraint. Our empirical analysis, based on Italy, shows that the Italian government is meeting its intertemporal budget constraint, in spite of the high levels of public debt. Nevertheless, the burden of correcting budgetary disequilibria is entirely carried out by changes in the average tax rate, with a weakly exogenous government spending, possibly determined by the political process. We document some rigidities of the tax instrument, in terms of downward inflexibility of the average tax rate, not only with respect to its long-run level, but also during periods of decreasing economic growth. Further, we provide some evidence in favour of a non-linear adjustment towards a sustainable long-run equilibrium, as the average tax rate adjusts faster the farther away it is from the equilibrium.
Keywords: C32; C51; C52; H20; H50; 330; intertemporal budget constraint; sustainability; non-linear error-correction; fiscal reaction function; Finanzpolitik; Budgetrestriktion; Nachhaltigkeit; Öffentliche Ausgaben; Steuerpolitik; Reaktionsfunktion; Intertemporale Allokation; Öffentliche Schulden; Schätzung; Italien